Exploring EFL Students’ Difficulties in Writing Compare and Contrast Essays - Puan Tursina; Silmawati; Zuhri Efendi (STMIK Indonesia Banda Aceh, 2026)
This study employed a descriptive quantitative research design to examine second-year university EFL students’ perceptions of difficulties in organizing compare and contrast essays. The research aimed to identify which parts of the essay; introduction, body, or conclusion that students perceive as most challenging and to explore specific difficulties encountered in writing each section. A total of 40 second year university students participated in the study. Data were collected using a validated questionnaire administered via Google form after the midterm examination. Descriptive statistics, particularly percentage analysis, were used to analyze students’ responses. The findings indicate that students perceived the body paragraph as the most challenging section, primarily due to difficulties in organizing ideas coherently, developing supporting details, and using appropriate transitions. In contrast, students expressed higher confidence in writing the introduction and conclusion, demonstrating familiarity with thesis formulation, hooks, and summarizing key points. These results suggest that EFL instruction should emphasize strategies for improving coherence, paragraph organization, and transitional skills, particularly in body paragraphs, to enhance students’ overall essay writing performance.